Estimation of catastrophic expenditure on oral health care among the residents of Sunsari district. - Dhakal,Sarita (2018)
ABSTRACT: Introduction: Oral health is the major public health problem worldwide. The cost of the treatment for oral health is high and majority of the expenses is made through out of pocket payment. This imposes a financial burden on the family and may lead to the financial catastrophic. This study aims to estimate the catastrophic oral health expenditure among the residents of Sunsari district and to assess its associated factors. Methodology: A community based cross-sectional study was conducted among two hundred four households of Sunsari district who have sought oral health care in the past three months. Information regarding household expenditure, oral health-seeking behavior, oral health care expenditure and coping strategies were obtained from the household member >18 years of age. The catastrophic threshold was estimated using Receiver's operating characteristics curve. Results: The catastrophic threshold for oral health care was estimated to be 7.5%. Around one fifth 925.5%) of the house hold reported having catastrophic oral health expenditure in the past three months before the interview. The mean out of pocket expenditure for oral health care was found to be NPR. 3288.2. Undergoing root canal treatment and total cost of the treatment was found to be associated with the catastrophic oral health expenditure. Conclusion: Oral health care adds a financial burden to the family forcing them towards catastrophe. Measures to reduce the economic burden should be applied. Prevention is better than cure. So, Preventive approaches to improve the oral health of the general population need to be addressed to reduce the catastrophic expenditure in oral health care. Keywords: Oral health care, Catastrophic, Oral health expenditure, Out of Pocket Payment